Hotel "Majestic" as the First Boutique Hotel in Serbia - Zivkovic, Dragan; Simonović Alfirević, Sanja; Gogic, Sanja (Arhitektura i urbanizam, 2021)
At the time it was built, Hotel Majestic set the standards of an elite hotel and a high level of hotel service in Serbia. Its owner, also the designer of the hotel, Milan Minić, has fully realized his intention, to separate his hotel from the group of other hotels, to become an elite and fashionable meeting place of Belgrade and world high society. The building is a combination of architecture, fine and applied arts and at the same time represents high standards in design, construction and interior design, which makes it a significant authorial achievement of Belgrade’s interwar architecture. The aim of this research is to analyze the architectural, urban, artistic and other characteristics of the Hotel Majestic building, in order to re-examine the view that Hotel Majestic was the forerunner of modern boutique hotels and thus decades ahead of its time. Many authors have written about the characteristics of a boutique hotel, but the clear definition of the concept still remains vague. By comparative analysis of the available literature and summarizing the results of this research, it can be concluded that Hotel Majestic fully meets all relevant criteria by which a boutique hotel can be recognized. The contribution of this research in the theoretical sense is reflected in the analysis and systematization of the most important interpretations of the concept of boutique hotels, as well as their basic characteristics. In the historiographical sense, the research provides a new insight into the hitherto unexplored area of ​​boutique hotels in Serbia. Guidelines for further research could be directed towards discovering new examples of boutique hotels, as well as towards closer definition and introduction into legal regulations.